STRATEGI PEMBELAJARAN AKTIVITAS RITMIK DI SD KRISTEN ANUGERAH HAUKOTO KOTA KUPANG - Veramyta Maria Martha Flora Babang; Maria Andriani Barek Ladjar; Ratni Elsi Fobia (Nusa Cendana University, 2022)
The purpose of this research is to describe and describe the Rhythmic Activity Learning Strategy implemented at Anugerah Haukoto Christian Elementary School, Kupang City. This research is a qualitative descriptive study. The method used is interview, observation and documentation. This study resulted in learning strategies for rhythmic activities at Anugerah Haukoto Christian Elementary School including: (1) teachers who have skills and abilities, high enthusiasm and motivation, and are able to overcome difficulties in overcoming rhythmic gymnastics learning to students. (2) students who have interest and motivation to take part in rhythmic gymnastics learning.